2023
DOI: 10.53855/bjt.v26i1.444_eng
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab plus Bevacizumab as a Bridge for Liver Transplant in Hepatocellular Carcinoma

Abstract: We report the case of a 68-year-old male with alcohol-related cirrhosis, diagnosed with hepatocellular carcinoma (HCC) not eligible for liver transplant. After immunotherapy with atezolizumab associated with bevacizumab, he underwent a successful living donor liver transplantation (LT), not showing disease evidence or graft injury, maintaining clinically and radiologically stable 14 months after surgery. This is a successful report of combined atezolizumab plus bevacizumab being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…We have collated data from all reported patients who received checkpoint inhibitors just before liver transplantation for HCC (Table 3). These include 4 case series [79][80][81][82] and various single case reports [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]. Altogether, rejection occurred in 8 out of 41 patients, in which there were 2 deaths[89,95] and 1 requiring re-transplant [81,83].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have collated data from all reported patients who received checkpoint inhibitors just before liver transplantation for HCC (Table 3). These include 4 case series [79][80][81][82] and various single case reports [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]. Altogether, rejection occurred in 8 out of 41 patients, in which there were 2 deaths[89,95] and 1 requiring re-transplant [81,83].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Red: patients who died from rejection. Green: data from Chouik et al, 98 Solino et al, 88 and Sogbe et al, 85 where the exact washout period was not reported.…”
Section: Author and Yearmentioning
confidence: 99%
See 1 more Smart Citation